PERANAN PROTOKOL MONTREAL 1987 DALAM MENANGGULANGI EFEK RUMAH KACA DI INDONESIA - Silalahi, Tania Yosefin Agustina; Sutiarnoto, Sutiarnoto; Suhaidi, Suhaidi (Journal of USU International Law, 2020)
ABSTRACT Tania Yosefin Agustina Silalahi * Dr. Sutiarnoto, SH. M.Hum ** Prof. Dr. Suhaidi, SH. M.H *** The international community for the first time raised the agenda in international relations which was marked by the holding of the United Nations (UN) convention in 1972 in Stock Holm, Sweden as an early milestone in saving the environment globally. The Montrea Protocol Convention; 1987 was formed due to the industrial revolution that occurred on a large scale, especially in European countries. In its agreement the Montreal Protocol has been revised 7 times, including in 1990 in London, 1991 in Nairobi, 1992 in Copenhagen, 1993 in Bangkok, 1995 in Vienna, 1997 in Montreal and 1999 in Beijing. It is believed by the international community that layers of ozone are expected to recover by 2050. Some of the ozone-depleting substances controlled by this agreement include CFC (Cholorofluorocarbon), Hallon, Tetrachlorite, Methyl Chlorofome, Hydro, Cholorofluorocarbon (HFC) and Methyl Bromide. The aim of this agreement is to realize that emissions worldwide can significantly deplete and reduce the ozone layer which impacts on human health and the environment, determined to protect the ozone layer by taking precautions to control global emissions. This agreement has been ratified by the Republic of Indonesia since 1992 with Presidential Decree No. 23 of 1992. In this case the Montreal protocol is one of the agreements responsible for the recovery of the ozone layer. This research is a normative legal research. To obtain accurate and in-depth data as desired by referring to the nature of the assessment developed in this research, data collection techniques are used through literature study where the data is collected through books, journals or writings or scientific articles. The results of this study indicate that around the 1970s environmental issues were considered and for the first time were raised as an agenda in international relations which was marked by the convening of the United Nations Conference (UN) in 1972 in Stockholm Sweden which was the first milestone in saving the environment globally. The 1987 Montreal Protocol has been revised seven times and has been ratified by 196 countries. The position of the 1987 Montreal Protocol in this agreement was made as a bulwark in controlling ozone depleting substances and replacing them with safer materials. This agreement is designed to implement climate change which aims to stabilize the concentration of greenhouse gases that are expected to tackle the greenhouse effect in preventing, depletion of the ozone layer which is expected to be better. Indonesian prospects after implementing the Montreal 1987 Protocol will bring many opportunities for Indonesia, in terms of environment, the ozone layer will increasingly recover and the side effects of ozone layer depletion such as UV-B rays will be reduced, not only in terms of the environment, good prospects will arise in terms of the economy where local companies switch to environmentally friendly technology or green industry will be more many innovations to be able to compete in the market Keywords: Ozone, Greenhouse Effect and Ozone Layer Depletion * University of North Sumatra University Faculty of Law students ** First Advisor of the Faculty of Law, University of North Sumatra *** Supervisor II of the Faculty of Law, University of North Sumatra